simplify. 5^-1(3^-2)

a) 45
b ) 1/45
c ) 15^-3
d ) 15^2

1 answer

To simplify 5^-1(3^-2), we can use the rule that says a^(-b) is equal to 1/a^b.

Therefore, 5^-1 is equal to 1/5^1 and 3^-2 is equal to 1/3^2.

Using these, we have:

5^-1(3^-2) = (1/5^1)(1/3^2) = (1/5)(1/9) = 1/(5*9) = 1/45

Therefore, the simplified form is option b) 1/45.
Similar Questions
  1. 1. Simplify 5^-1(3^-2)A. 45 B. 1/45 C. 15^-3 D. 15^2 2. Simplify (3xy^3)^2(xy)^6 A. 9x^8y^12 B. 3x^8y^12 C. 2x^3y^12 D. 9x^8y^9
    1. answers icon 7 answers
  2. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  3. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  4. Simplify 8a − 2a.Simplify 12e − 5f − 7e +3f. Simplify 9x + 3y − 6 − 5x + 4y −3. Simplify 9/11z − 4/11z. Simplify
    1. answers icon 4 answers
more similar questions